2016
DOI: 10.1093/mnras/stv2949
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a change in the dominant satellite galaxy quenching mechanism atz = 1

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
230
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(282 citation statements)
references
References 106 publications
(187 reference statements)
49
230
1
1
Order By: Relevance
“…Van der Burg et al (2013), Kovač et al (2014), and Balogh et al (2016) have found that the environment plays an important role in determining the star formation activity of satellites, at least up to z ∼ 1. However these works have only probed relatively massive haloes (M h 10 13 M ⊙ ).…”
Section: Passive Fractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Van der Burg et al (2013), Kovač et al (2014), and Balogh et al (2016) have found that the environment plays an important role in determining the star formation activity of satellites, at least up to z ∼ 1. However these works have only probed relatively massive haloes (M h 10 13 M ⊙ ).…”
Section: Passive Fractionsmentioning
confidence: 99%
“…This parameter, sometimes called the satellite quenching efficiency, quantifies the fraction of galaxies that had their star formation activity quenched by environment specific processes since they accreted as satellites into a more massive halo (see also Kovač et al 2014;Hirschmann et al 2014;Balogh et al 2016). It is defined as:…”
Section: Satellite Quenching Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Since we only observe environmental effects within the dense groups of this protocluster, this suggests that environmental effects will become more prominent simply due to the hierarchical growth of clusters. However, this picture is too simplistic as the mechanism that quenches satellite galaxies may not be the same in the distant and local Universe (Balogh et al 2016).…”
Section: The Evolution Of Environmental Effects In Protoclustersmentioning
confidence: 99%
“…By way of secular cluster processes, blue galaxies of different masses and brightnesses are shown to transition on different timescales across different epochs (e.g. Balogh et al 2016;Muzzin et al 2014;Ilbert et al 2015). A variety of short and long-term mechanisms could result in a starburst in the past ∼1 Gyr followed by rapid quenching, to produce the current post-starburst population.…”
Section: Discussionmentioning
confidence: 99%